Factors Associated with the Macular Ganglion Cell–Inner Plexiform Layer Thickness in a Cohort of Middle-aged U.S. Adults. Issue 3 (March 2021) - Paulsen, Adam J.; Pinto, Alex; Merten, Natascha; Chen, Yanjun; Fischer, Mary E.; Huang, Guan-Hua; Klein, Barbara E. K.; Schubert, Carla R.; Cruickshanks, Karen J.
Abstract : SIGNIFICANCE: The macular ganglion cell–inner plexiform layer (mGCIPL) may serve as a quick and easily obtained measure of generalized neurodegeneration. Investigating factors associated with this thickness could help to understand neurodegenerative processes. PURPOSE: This study aimed to characterize and identify associated factors of the mGCIPL thickness in a Beaver Dam Offspring Study cohort of middle-aged U.S. adults. METHODS: Baseline examinations occurred from 2005 to 2008, with follow-up examinations every 5 years. Included participants had baseline data and measured mGCIPL at 10-year follow-up (N = 1848). The mGCIPL was measured using the Cirrus 5000 HD-OCT Macular Cube Scan. Associations between mean mGCIPL thickness and thin mGCIPL, defined as 1 standard deviation (SD) below the population mean, and baseline risk factors were investigated using generalized estimating equations. RESULTS: Participants (mean [SD] baseline age, 48.9 [9.3] years; 54.4% women) had mean (SD) mGCIPL thicknesses of 78.4 (8.1) μm in the right eye and 78.1 (8.5) μm in the left (correlation coefficient = 0.76). In multivariable models, age (−1.07 μm per 5 years; 95% confidence interval [CI], −1.28 to −0.86 μm), high alcohol consumption (−1.44 μm; 95% CI, −2.72 to −0.16 μm), higher interleukin 6 levels (50% increase in level: −0.23 μm; 95% CI, −0.45 to 0.00 μm), myopia (−2.55 μm; 95% CI, −3.17 to −1.94 μm), and glaucoma (−1.74 μm; 95% CI, −2.77 to −0.70 μm) were associated with thinner mGCIPL. Age (per 5 years: odds ratio [OR], 1.38; 95% CI, 1.24 to 1.53), diabetes (OR, 1.89, 95% CI, 1.09 to 3.27), myopia (OR, 2.11; 95% CI, 1.63 to 2.73), and increasing and long-term high C-reactive protein (ORs, 1.46 [95% CI, 1.01 to 2.11] and 1.74 [95% CI, 1.14 to 2.65], respectively) were associated with increased odds of thin mGCIPL. CONCLUSIONS: Factors associated cross-sectionally with mGCIPL thickness, older age, high alcohol consumption, inflammation, diabetes, myopia, and glaucoma may be important to neural retina structure and health and neuronal health system-wide. Abstract : Supplemental digital content is available in the text.